Nematodes from galls on Myrtaceae. VIII. Fergusobia from small galls on shoot buds, with descriptions of four new species - Davies, Kerrie A.; Bartholomaeus, Faerlie; Giblin-Davis, Robin M.; Ye, Weimin; Taylor, Gary S.; Thomas, W. Kelley (Zootaxa, 2014)
Small shoot bud galls induced by the Fergusobia (Nematoda: Neotylenchidae)/Fergusonina (Diptera: Fergusoninidae) mutualism occur on various Eucalyptus spp. Four new species of Fergusobia, collected from small shoot bud galls on Eucalyptus camaldulensis, E. gomphocephala and E. leucoxylon, are described. Fergusobia gomphocephalae Davies n. sp. is morphologically characterized by a combination of a small C-shaped parthenogenetic female with a variable, conoid tail, a small C-shaped infective female with a hemispherical tail tip, and an arcuate or J-shaped male with a broad tail, angular spicule and short peloderan bursa. Fergusobia leucoxylonae Davies n. sp. has a C-shaped parthenogenetic female with a conoid tail with a narrowly rounded tip, an arcuate infective female with a broadly rounded tail tip, and an almost straight to barely J-shaped male with angular (not heavily sclerotised) spicule and short bursa. Fergusobia schmidti Davies & Bartholomaeus n. sp. has an arcuate to open C-shaped parthenogenetic female with a relatively large body diameter, relatively long stylet and small tail with a broadly rounded tail tip, an open C-shaped infective female with a broadly rounded to hemispherical tail tip, and an arcuate to barely J-shaped male with spicules angular at about 33% of their length and peloderan bursa arising at about half body length. Fergusobia sporangae Davies n. sp. has an arcuate to open C-shaped parthenogenetic female with a relatively long stylet and a broadly rounded tail tip, an arcuate infective female with a short tail with a broadly rounded to hemispherical tip, and an arcuate to barely J-shaped male with angular (not heavily sclerotised) spicule and short peloderan bursa. Various forms of small shoot bud galls are described. From phylogenetic analyses based on sequences of the D2/D3 expansion segment of the large subunit rRNA gene, the four new species belong to two sister clades of Fergusobia. The larval shield morphology of their associated fly species and possible genetic relationships are discussed.